2010
DOI: 10.1111/j.1365-2745.2010.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant–soil feedbacks contribute to an intransitive competitive network that promotes both genetic and species diversity

Abstract: Summary1. Plant communities are generally thought to follow strict competitive hierarchies, in which species can be linearly ordered according to their ability to compete for a few limiting resources. Such strict hierarchies should lead to reduced diversity, since the single best competitor will eventually exclude the other species. However, more complex dynamics may emerge if different plant species or genotypes compete in different ways, such as through the release of toxic allelochemicals or the alteration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 51 publications
2
77
0
Order By: Relevance
“…First, plant genotypes are known to influence microbial communities [18,19]. Second, plantsoil feedbacks can contribute to plant-plant competitive interactions and coexistence [41][42][43], and recent studies suggest that plant-soil feedbacks can contribute to fitness differences among plant genotypes within a species [18,44]. Finally, eco-evo dynamics are expected to occur when organisms have large effects on their environment and as a result can alter the selective environment for themselves and other species in the community (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…First, plant genotypes are known to influence microbial communities [18,19]. Second, plantsoil feedbacks can contribute to plant-plant competitive interactions and coexistence [41][42][43], and recent studies suggest that plant-soil feedbacks can contribute to fitness differences among plant genotypes within a species [18,44]. Finally, eco-evo dynamics are expected to occur when organisms have large effects on their environment and as a result can alter the selective environment for themselves and other species in the community (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While declines in AMF infection rates of native species would seemingly have negative fitness effects, it is not always clear that changes in AMF community composition, when seen, will necessarily have negative effects on competing plants (but see Lankau, 2011a). Providing additional support for potentially important allelopathic effects are reports of the impact of other weedy Brassicaceous species on mycorrhizae, including that of Brassica nigra (Lankau et al, 2011) and Sysimbrium loeselii (Bainard et al, 2009), but none of these cases have been as fully developed as that of Alliaria, and may be subject to the same limitations that intensive study of this species has revealed. The role of glucosinolates in effects of Brassicaceous species on mycorrhizae also remains to be fully elucidated.…”
Section: Allelopathic Effects On Beneficial Microbesmentioning
confidence: 95%
“…The reason for the negative impact of sinigrin on heterospecific plants can, at least partly, be explained by the toxic effects of sinigrin on mycorrhizal fungi in the soil. Most heterospecifics benefit from mycorrhiza association, whereas Brassica is non-mycorrhizal and hence not affected by reduced mycorrhizae in the soil [31]. High concentration genotypes are favoured when B. nigra is rare and most often competes against heterospecifics but are disfavoured as B. nigra becomes more abundant and increasingly competes against conspecifics.…”
Section: Plant Species Coexistence: Insight From Theorymentioning
confidence: 99%